TEKNO-CULTURE: MEMAHAMI KONDISI MASYARAKAT MASA DEPAN - Aswan Aswan (Palita: Journal of Social Religion Research, 2017)
The development of advanced communications technology has brought about fundamental changes in the world of life. A number of views on the spirit behind the progress are emerging, as well as about the effects it incurs. This paper tries to see two basic things. First about the passion and trends behind the advances in communication technology. This section includes all-free behavior that encourages the tendency of abnormalities, identity greed, the speed and interconnectedness. Second, about the spirit of thought that underlies the advancement of communication technology. This section reviews the three currents of thought that become the dominant discusus in viewing technology. That thought is; 1) utopianism as an optimistic view of the positive role of science and technology, 2) dystopianism, as a pessimistic view of science and technology, and 3) hypertopianism, as the 'fatalist' view of science and technology. The various streams of thought that the author studied from a number of literatures in this field show the tendency of many thinkers to highlight the negative aspects of the latest advances in communication technology. Similarly depicted in this paper, the gloomy portrayal of the future of communication technology in this paper can be viewed positively, that it gives us a map of the spirit of progress, as a "long-warning system" that provides mapping, and the possibility of the future by departing from current social, cultural and technological trends can help us read its constellations and impacts